PELAYANAN ADMINISTRASI INTERKATIF BERBASIS DIGITAL MASYARAKAT NAGARI AMPALU KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA: PELAYANAN ADMINISTRASI INTERKATIF BERBASIS DIGITAL MASYARAKAT NAGARI AMPALU KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - Farmila, Rini (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
In the post-Covid 19 era, interactive digital-based public services are one of the efforts to overcome the limitations of direct public services for the convenience of the community after Covid and to keep up with the times. So that digital innovation is needed in public services to be effective and efficient, this study attempts to identify quality indicators and obstacles in the implementation of e-government in the post-Covid 19 IT era. The research method used in this study is the library research method. The study was conducted by collecting data through documentation techniques and online data searches, using content analysis techniques. Based on the results of the search, the author found that the use of e-government still requires consolidation and maturation in terms of service quality in terms of efficiency, trust, reliability, and community support. The implications of this study can be used as consideration and input for the government to improve the quality and innovation of digital-based public services. The recommendations in this study are that improvements are needed to the application server and government website, to carry out continuous socialization and require the readiness of solid and experienced human resources, especially in the field of technology. Keywords: Administrative Services, Interactive, Digital-based